2000
DOI: 10.1046/j.1365-3016.2000.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and glucose intolerance during pregnancy among Mexican‐Americans

Abstract: Low birthweight is uncommon among Mexican-American infants, despite the substantial proportion of mothers who live in poverty. This apparent paradox has generated studies of factors protecting fetal growth, but may have masked other important health problems in the Mexican-American community. Obesity, impaired glucose tolerance and diabetes are common among Mexican-American women of childbearing age and during pregnancy. Prevalence of these conditions is two to four times higher in Mexican-American than in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
1
4
0
2
Order By: Relevance
“…Each additional point of BMI was associated with an increase of 0.52 mg/dL (95% CI 0.41 to 0.63, p < 0.001). Hispanic ethnicity was associated with an increase of 6.69 mg/dL (95% CI 4.53 to 8.85 mg/dL, p < 0.001) as previously reported 27 . Demographics are described in Table S4.…”
Section: Resultssupporting
confidence: 84%
“…Each additional point of BMI was associated with an increase of 0.52 mg/dL (95% CI 0.41 to 0.63, p < 0.001). Hispanic ethnicity was associated with an increase of 6.69 mg/dL (95% CI 4.53 to 8.85 mg/dL, p < 0.001) as previously reported 27 . Demographics are described in Table S4.…”
Section: Resultssupporting
confidence: 84%
“…In the year 1990, the health problems associated with either too low or excessive pregnancy weight gain lead the Institute of Medicine (IOM) to publish its weight gain guidelines [52]. Recently, several medical papers evaluate the compliance with these guidelines and stress the role of comprehensive prenatal care in meeting the IOM goals [53][54][55][56][57]. With the spread of the 'obesity epidemic' in the US, the association between excessive weight gain and weight retention and obesity is receiving special attention.…”
Section: Why Study Maternal Health?mentioning
confidence: 99%
“…With the spread of the 'obesity epidemic' in the US, the association between excessive weight gain and weight retention and obesity is receiving special attention. It has been found that the prevalence of excessive weight gain is high [53,57] and that substantial racial disparities exist [54,56]. Evidence from clinical trials on the potential role of prenatal care in dealing with these issues is encouraging, however.…”
Section: Why Study Maternal Health?mentioning
confidence: 99%
“…Повећан прираст телесне масе је био учесталији код трудница прекомерне телесне масе, овакве резултате су потврдиле и друге студије (17,18) . У овој студији смо пронашли да труднице прекомерне телесне масе имају значајно повећан ризик за појаву гестацијског дијабетеса, што су приметили и други аутори (11,(19)(20)(21)(22)(23) . Такође је примећено чешће јављање гестацијског дијабетеса код вишеротки, што се може повезати са већом инциденцом јављања прекомерне телесне масе код њих.…”
Section: дискусијаunclassified